2016
DOI: 10.3389/fpsyg.2016.01941
|View full text |Cite
|
Sign up to set email alerts
|

What Makes for the Most Intense Regrets? Comparing the Effects of Several Theoretical Predictors of Regret Intensity

Abstract: Several theories have been proposed to account for variation in the intensity of life regrets. Variables hypothesized to affect the intensity of regret include: whether the regretted decision was an action or an inaction, the degree to which the decision was justified, and the life domain of the regret. No previous study has compared the effects of these key predictors in a single model in order to identify which are most strongly associated with the intensity of life regret. In this study, respondents (N = 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…They found that the most intense life regrets reflect the core motive of affiliation, for example love regrets, friendship regrets, and regrets about not phoning mom last week. Regrets relating either to affiliation or achievement dominated over other kinds of life regrets, but affiliation regrets were felt more intensely than achievement regrets (see Towers, Williams, Hill, Philipp, & Flett (2016) for further supportive evidence). In probing this pattern further, Morrison et al found that when people felt threatened by life circumstances that challenged their relationships, they reported more intense life regrets.…”
Section: Counterfactuals Are About Goalsmentioning
confidence: 94%
“…They found that the most intense life regrets reflect the core motive of affiliation, for example love regrets, friendship regrets, and regrets about not phoning mom last week. Regrets relating either to affiliation or achievement dominated over other kinds of life regrets, but affiliation regrets were felt more intensely than achievement regrets (see Towers, Williams, Hill, Philipp, & Flett (2016) for further supportive evidence). In probing this pattern further, Morrison et al found that when people felt threatened by life circumstances that challenged their relationships, they reported more intense life regrets.…”
Section: Counterfactuals Are About Goalsmentioning
confidence: 94%
“…According to Decision Justification Theory, individuals tend to experience more intense regret when they do not see their decision as justifiable (Connolly & Zeelenberg, 2002). In fact, many studies have shown a negative relationship between the level of justification and regret intensity (Inman & Zeelenberg, 2002;Pieters & Zeelenberg, 2005;Reb & Connolly, 2010;Towers et al, 2016). Hence, compared to satisficers, maximizers' decisions might reflect a more cautious, reflective, or justifiable process, which theoretically should lead to less regrettable decisions.…”
Section: Discussionmentioning
confidence: 99%
“…All measures were on a 7-point Likert scale (1 = not at all, 7 = completely). Regret attributions were measured first with one item adapted from Towers et al (2016) Clark et al (2018): 'Indicate how much Mr. Smith decision to take this route was freely chosen', 'Indicate how much Mr. Smith could have made other choices', and 'Indicate how much the fact that Mr. Smith took this route was due to his own free choice'. We averaged the three items measuring free will attributions (α = 0.73 and 0.83, for the routine and exceptional condition, respectively).…”
Section: Methods Preregistrationmentioning
confidence: 99%